Verbalization of Music Processes (The Engine of thought Experiment in the Music of the Early-Modern Period) (International Journal of Psychosocial Rehabilitation, 2020)
Thematic justification: The most important source and carrier of hidden non-verbalized meanings is music. It can penetrate the innermost layers of consciousness and being that are fundamentally inaccessible to scientific knowledge. Therefore, nonverbal thinking, as well as nonverbal methods of obtaining information, is increasingly becoming the subject of scientific research. Under the conditions of the rise of personal and universal issues, the search for a solution to not only these problems but also the exposure and study of rational tools for comprehending the world through verbalization of musical processes becomes essentially important. Purpose: To reveal and verbalize rational algorithms constituting musical creative activity. Methods: The presented article employed various methods of dialectical logic, phenomenology, comparative studies, the system-structural method that considers the literary text as a semiotic system, and general scientific research methods (abstracting, idealization, modeling, and extrapolation). Results: It was established that the engine of a thought experiment is the basis of rational algorithms of the art music It was proved that the development of musical thought in the music of the Early Modern Period obeys dialectical logic of ascent from the abstract to the concrete. The most important stages of a thought experiment in a musical text were described, and an idealized object was identified. Methods of transformation and modification of an idealized subject were revealed, and specific methods of transformation of an idealized subject in music were established. The commonality of transformations of an idealized subject in mathematics and music was emphasized. Conclusions: The identification of the meaning-creating mechanisms of musical creativity by revealing the possibilities of a thought experiment allows realizing the aesthetic principles and ideals of musical culture, as well as predicting its further development. The study established the commonality of thought processes in scientific knowledge and artistic creativity. It was also revealed that the verbalization of musical processes stimulates the development of promising areas that allow real integration of philosophical and musicological approaches with regard to the problem of a thought experiment.